Satisfaction Levels concerning Current Chronic Constipation Treatment Options in Saudi Arabia. (2nd January 2020) - Alhossan, Abdulaziz; Alrabiah, Ziyad; Alghadeer, Sultan M.; Wajid, Syed; Al-Arifi, Mohamed N.; Babelghaith, Salmeen D.
Abstract : Background and Aim . Chronic constipation is frequently underreported as people with obstruction do not generally seek medical advice. This study was aimed at determining the prevalence of chronic constipation and assessing satisfaction with current chronic constipation treatment options. Methods . This study was undertaken in Riyadh City, Saudi Arabia, in April 2019. The study population comprised respondents aged ≥18 years who had been recruited to participate through advertising on social media. Results . Of 532 respondents who completed our questionnaire, 153 (25.4%) had constipation, based on listed criteria, and of these, 121 (22.7%) reported having been constipated for ≥6 months; nearly 48% reported having been constipated for >3 years, while 63.6% of those chronically constipated were female. Bisacodyl was the laxative medication most used to treat chronic constipation, and 17.4% of users reported that they had used laxative medication for >12 months. Complementary and alternative medicines (CAMs) were utilized in 44.4% of respondents with chronic constipation. There was a significant association between the group who used CAMs and age (p = 0.013 ). Drinking water was the most common CAM adopted for those experiencing chronic constipation, followed by consumption of fiber (35.5%) and senna (19.8%).